Sensor Measures of Affective Leaning - Martens, Thomas; Niemann, Moritz; Dick, Uwe (Frontiers in Psychology, 2020)
The aim of this study was to predict self-report data for self-regulated learning with sensor data. In a longitudinal study multilevel data were collected like self-report data with questionnaires and embedded experience samples as well as sensor data like electrodermal activity and EEG. 101 students from a private university in Germany performed a learning experiment followed by final measures of intrinsic motivation, self-efficacy and gained knowledge. During the learning experiment psychophysiological data like electrodermal activity (EDA) combined with embedded experience sampling measuring motivational states like affect and interest every 270 seconds. Results of machine learning models show that consumer grade wearables for EEG and EDA failed to predict embedded experience sampling. EDA failed to predict outcome measures as well. This gap can be explained by some major technical difficulties, especially by lower quality of the electrodes. Nevertheless, an average activation of all EEG bands at T7 (left-hemispheric, lateral) can predict lower intrinsic motivation as outcome measure. This is in line with the PSI-theory of Julius Kuhl. With more advances sensor measures it might be possible to track affective learning in an unobtrusive way and support micro-adaptation in digital learning environment.